Indonesian Geography Regional Study Results in UNP Students - Afdhal, Afdhal; Ananda, Azwar; Mukhaiyar, Mukhaiyar; Gusril, Gusril (Sumatra Journal of Disaster, Geography and Geography Education, 2020)
Regional Geography Indonesia courses are subject areas of expertise in the Department of Geography FIS UNP. Based on an initial survey of learning outcomes in the Regional Geography Indonesia course in the last five years it was revealed that the achievement of learning outcomes was classified as low to moderate. Students who mastered the material 85% not more than 15% students and the average student who mastered the material 68%, meaning that students get a value of B. This study aims to determine the direct and indirect influence of the use of learning resources, the ability to read maps and socioeconomic status as well as learning motivation towards the learning outcomes of Indonesian Regional Geography. The research method used is quantitative with a path analysis approach. The population of this research is all students majoring in Geography who have taken Indonesian Regional Geography courses totalling 507 people. The research sample was drawn by proportional random sampling of 84 respondents. The analysis shows the use of learning resources (X1) the ability to read maps (X2) socioeconomic status (X3) and motivation to learn (Y), which directly or indirectly influence the regional learning outcomes of Indonesian geography (Z).